Rethinking teaching activity and the development of collaborative practices at school (Olhar de Professor, 2011)
This article presents an e-learning experience in which a Web based learning community has been developed to gather several teacher educators of the course Normal Superior/PROFORMAR, with the digital support of the Moodle platform. During the research process it was possible to understand the restrictions and the perspectives of distance education in the state of Amazonas. The theoretical guidelines of this project are in line with the studies on Teachers Continuing Education, but with a critical and emancipating perspective. The studies relative to the new demands of the teaching activity were the starting point of the study, particularly those that stated the need to rethink the teaching activity and the development of collaborative practices at school using technological resources. Thus, the discussion started by raising relevant questions. Following this, all the issues that can condition adjustments in our profession are presented, seeking to show the demands requested by the office of teaching as well as their obstacles. Finally, the experiences obtained with the development of the project are discussed.
Keywords: Communities; Learning; Training; Teacher.